A novel high-yield process of phospholipase D-mediated phosphatidylserine production with cyclopentyl methyl ether. (March 2018) - Qin, Wen; Wu, Chengjin; Song, Wei; Chen, Xiulai; Liu, Jia; Luo, Qiuling; Liu, Liming
Graphical abstract: Highlights: Cyclopentyl methyl ether is an eco-friendly and green solvent that suitable for phosphatidylserine (PS) production. This novel process produces PS with high-efficiency and industrialized potential successfully. The phospholipids are easily purified from cyclopentyl methyl ether by evaporation. The biocatalyst is available and productive. Abstract: In this study, an eco-friendly and high-efficient method for the bioconversion of phosphatidylserine (PS) from phosphatidylcholine (PC) and l -serine was developed. After the strain screening, the Streptomyces chromofuscus phospholipase D ( Sc PLD) was chosen and expressed in Escherichia coli BL21 with pET28a (+). After optimization, the maximal specific productivity and Sc PLD hydrolysis activity reached 9049.6 U/g and 10.6 U/mL, respectively, while induction with 2 g/L lactose, at 25 °C for 12 h. The maximal conversions of PC to PS was 93.4% with a final PS concentration of 106.2 g/L (53.1 g/L/h) under theoptimal conditions: 0.153 M PC in CPME, 2.3 M l-ser in sodium acetate buffer, 2.0 g lyophilized cells/mol PC, 100 mM Ca 2+, 40 °C, and 2 h of incubation. After scale-up to 1 L, the conversions and yield maintained at 85.4% and 97.2 g/L. Therefore, the enzymatic process showed great potential for industrialization of PS.